Quasi Horn Antenna Array for Ku Band Monopulse Radiation - Keskin, Ahmet Kenan; Tulum, Mehmet Akif; Turk, Ahmet Serdar (IEEE, 2016)
In this paper, a quasi-horn antenna array, which is combination of 4 x 4 slot array and its flares, is designed for Ku band monopulse radiation. The slots arc fed by waveguide power divider, in order to obtain sum and difference radiation pattern, a magic T is utilized end of the waveguide feeder. Slot dimensions and distance between each slot are adjusted and optimized to get high gain and low return loss using 3D EM simulation. Short depth flares are added to aperture of each 4 x 1 slots to enhance gain of the array. According to the simulation results, gain of the array at the sum port is 21.9 dBi. At the difference port, monopulse radiation pattern have 19.3 dBi maximum gain and 32 dB null. Return losses at the sum and difference port are lower than-6 dB in the operation band. Total dimensions of the 4 x 4 array are 8.36 cm x 8.4 cm x 7.06 cm.
Keywords: Quasi Horn; Dielectric Load; Slot Array; Ku Band; MICROSTRIP ANTENNA; PERFORMANCE; GAIN; Engineering; Telecommunications